Knowledge of Disease Management and Complication Prevention Among Type 2 Diabetes Mellitus Patients in Tangerang District - Agustina Saputri; Pasha Erica Tammu; Rizki Indra Irawan; Zefanya Stephanie Natalia (STIKep PPNI Jawa Barat, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with increasing prevalence. Patients' knowledge about T2DM is very important to prevent complications and improve quality of life. Objectives: The aim of this study is to assess the level of knowledge of patients with T2DM at Puskesmas Curug. Methods: The design of the study used a cross-sectional quantitative method with purposive sampling, and included 142 patients with T2DM who visited the Curug Health Center in February-April 2025. Data were collected using the Diabetes Knowledge Questionnaire (DKQ) consists of 24 items on three dimensions: baseline information, glycaemic control, and complications prevention. Results: Results showed that 66.9% of patients had low level of knowledge, with most female respondents (69%). Conclusions: The study concluded that the level of knowledge of patients with T2DM at Puskesmas Curug is still low. Specific educational programs need to be planned and implemented among the population for improvement in knowledge and disease management. Further research is recommended to explore factors influencing patient knowledge in order to make training interventions more effective.